Expanding Substance Use Treatment Options for HIV Prevention With Buprenorphine–Naloxone: HIV Prevention Trials Network 058. (15th April 2015) - Metzger, David S.; Donnell, Deborah; Celentano, David D.; Jackson, J. Brooks; Shao, Yiming; Aramrattana, Apinun; Wei, Liu; Fu, Liping; Ma, Jun; Lucas, Gregory M.; Chawarski, Marek; Ruan, Yuhua; et al.
Abstract : Background: Injection opioid use plays a significant role in the transmission of HIV infection in many communities and several regions of the world. Access to evidence-based treatments for opioid use disorders is extremely limited. Methods: HIV Prevention Trials Network 058 (HPTN 058) was a randomized controlled trial designed to compare the impact of 2 medication-assisted treatment (MAT) strategies on HIV incidence or death among opioid-dependent people who inject drugs (PWID). HIV-negative opioid-dependent PWID were recruited from 4 communities in Thailand and China with historically high prevalence of HIV among PWID. A total of 1251 participants were randomly assigned to either (1) a 1-year intervention consisting of 2 opportunities for a 15-day detoxification with buprenorphine/naloxone (BUP/NX) combined with up to 21 sessions of behavioral drug and risk counseling [short-term medication-assisted treatment (ST-MAT)] or (2) thrice-weekly dosing for 48 weeks with BUP/NX and up to 21 counseling sessions [long-term medication-assisted treatment (LT-MAT)] followed by dose tapering. All participants were followed for 52 weeks after treatment completion to assess durability of impact. Results: Although the study was stopped early due to lower than expected occurrence of the primary end points, sufficient data were available to assess the impact of the interventions on drug use and injection-related risk behavior. At week 26, 22% of ST-MAT participants had negative urinalyses for opioids compared with 57% in the LT-MAT ( P < 0.001). Differences disappeared in the year after treatment: at week 78, 35% in ST-MAT and 32% in the LT-MAT had negative urinalyses. Injection-related risk behaviors were significantly reduced in both groups after randomization. Conclusions: Participants receiving BUP/NX 3 times weekly were more likely to reduce opioid injection while on active treatment. Both treatment strategies were considered safe and associated with reductions in injection-related risk behavior. These data support the use of thrice-weekly BUP/NX as a way to reduce exposure to HIV risk. Continued access to BUP/NX may be required to sustain reductions in opioid use.